Advocacy non-governmental organizations (NGOs) resiliency to shrinking civic space in Tanzania - Rogers Rugeiyamu; Ajali Mustafa Nguyahambi (Journal of Humanities and Applied Social Sciences, 2024)
Purpose – The world is experiencing democratic backsliding such that the situation is down back to 1986. This has resulted in the global shrinking of civic space for civil society organizations (CSOs). NGOs engaging in advocacy activities are seen to be among the CSOs affected. Using four NGOs cases from Tanzania, the study contributes to the civic space debate by uncovering how advocacy NGOs become resilient. Design/methodology/approach – The study is anchored in interpretivism and a cross-sectional case study design, following a qualitative approach path. Data were collected through interviews and a documentary review. Findings – Results show that several strategies such as complying, building community back-up, collaboration, strategic litigation, using digital media and changing the scope are applied. However, strategies face obstacles including scope limitations, expected democratic roles, high cost, changes in the scope and being outsmarted by the government, and hence their effectiveness is questionable. Research limitations/implications – This study focused on advocacy NGOs. More studies can be conducted for other advocacy-related CSOs on how they become resilient. Practical implications – While NGOs are allowed to exist in the country, their freedom continue to be curtailed. Even the effectiveness of resiliency becomes temporary and depends on the political will of the existing regime. Originality/value – Tanzania NGOs have to build strong bonds with citizens, expand the scope of strategies and use deliberative democratic principles to educate the government to change laws and tolerate plural political culture. Also, NGOs in other countries with confined civic space can apply the same.